On Soft b-w-Open Sets (2020)
In this paper, it used the notions of soft ω-open sets to introduce and study the concepts of soft b-ω-open sets. Moreover, some of their properties are shown. Furthermore, the concepts of soft b-T1 and soft b-T2 spaces are defined. Also, it studies the relationships between the b-ω-open sets of a given indexed family of topological spaces and the soft b-ω-open sets of their generated soft topological space. Besides, With these concepts it might study new notions related to this such as soft Lindelof or soft weakly Lindelof in soft topological spaces.